(untitled) (Torani Journal of Fisheries and Marine Science, 2023)
This research aims to determine the types, characteristics, diversity and distribution patterns of sea cucumbers in Bajo Village, Tilamuta District, Boalemo Regency. This research was conducted for 3 months starting from August to October 2022. Data collection on sea cucumber was carried out at 3 stations with 3 quadrants at each station with a quadrant size 4×25 meters, samples were taken at low tide during the day and at night. In addition, measurements of the physical and chemical quality parameters of the waters were also carried out. Based on the results of the study, 9 species pf sea cucumbers were found in Bajo Village, Tilamuta Sub District: Holothuria scabra, Holothuria atra, Holothuria coluber, Holothuria fuscocinerea, Stichopus vastus/gammat, Holothuria hilla, Actinopyga miliaris, Bohadchia similis, and Synapta maculata. Moreover, the abundance of sea cucumbers in the waters of Bajo Village, Tilamuta Sub District, Boalemo Regency, was found during daytime sampling. The diversity of sea cucumbers in the waters of Bajo Village ranges from 1,59–1,89 which is included in the medium category according to the Shannon-Wiener. In short, the distribution pattern of sea cucumbers in the waters of Bajo Village is more dominant in living in groups.